Expectations formation, sticky prices, and the ZLB - Betsy Bersson; Patrick Hürtgen; Matthias Paustian (Deutsche Bundesbank, 2019)
At the zero lower bound (ZLB), expectations about the future path of monetary or fiscal policy are crucial. We model expectations formation under level-k thinking, a form of bounded rationality introduced by García-Schmidt and Woodford (2019) and Farhi and Werning (2017), consistent with experimental evidence. This process does not lead to a number of puzzling features from rational expectations models, such as the forward guidance and the reversal puzzle, or implausible large fiscal multipliers. Optimal monetary policy at the ZLB under level-k thinking prescribes keeping the nominal rate lower for longer, but short-run macroeconomic stabilization is less powerful compared to rational expectations.
Keywords: E32; 330; expectations formation; optimal monetary policy; New Keynesian model; zero lower bound; forward guidance puzzle; reversal puzzle; fiscal multiplier